Is it appropriate to use WHO Multicentre Growth Reference Study standards to assess the growth parameters of Sri Lankan babies? A single-centre cross-sectional study. Issue 1 (6th February 2018) - Abeyagunawardena, Ishanya Ayeshini; Abeynayake, Arundhi; Anuththara, Thushani; Alawaththegama, Kasun; Amanda, Sakuni; Abeyrathne, Vishaka; Amaradasa, Prabhadi; Anuradha, Buddhika; Ahmed, Hanan; Abeykoon, Chathupa; Fernando, Dinesh Malcolm Gerard
Abstract : Objective: To compare the anthropometric measurements of newborns in a tertiary care hospital in Sri Lanka, with WHO standards. Methods: Birth weight, length and occipitofrontal circumference (OFC) of 400 consecutive, term newborns of healthy mothers were measured in a tertiary care hospital. Results: 400 subjects were approached and seven were excluded, concluding the study population to 184 boys and 209 females. Medians of birth weight, length and OFC were 3000 g, 49.95 cm and 34.15 cm of males and IQRs were 555.00, 2.70 and 1.70, respectively. For females, the medians of birth weight, length and OFC were 2900 g, 48.9 cm and 34.00 cm with IQRs of 450.00, 2.70 and 1.50, respectively. The two-tailed t-test revealed that median weights of males (t=9.632) and females (t=12.04) and OFC of males (t=3.98) were significantly lower than the WHO medians. There was a significant association of birth weight, with mother's prepregnancy weight, in males (β coefficient=12.629 with 95% CI 6.275 to 18.982) and females (β coefficient=5.880, 95% CI 1.434 to 10.325). Significant associations of length (β coefficient=0.046, 95% CI 0.012 to 0.080) and OFC (β coefficient=0.033, 95% CI 0.014 to 0.053) with mother's prepregnancy weight in males and length (β coefficient=0.084, 95% CI 0.022 to 0.145) and weight (β coefficient=10.780, 95% CI 0.93 to 20.629) with maternal age in females were found. Furthermore, birth weight in males was significantly associated with maternal height (β coefficient=10.899, 95% CI 0.552 to 21.247). Education level, ethnicity and parity showed no significant associations with above parameters. Conclusion: The median weights of both sexes and OFC in males were significantly lower than the WHO standards. Island-wide studies are indicated to evaluate the appropriateness of applying WHO standards to Sri Lankan newborns.